THE INFLUENCE OF GENDER ROLE IDENTITY TO LEADER MEMBER EXCHANGE: EMOTIONAL INTELLIGENCE AS INTERVENING VARIABLE - Marsha Artha Santoso; Rosaly Franksiska (Indonesian Journal Of Business And Economics, 2019)
Leader-Member Exchange (LMX) is a reciprocal relationship between leaders and subordinates. The high quality of LMX will have a good impact on the progress of an organization. This research is quantitative research to examine the effect of gender role identity: masculinity on the leader-member exchange (LMX) with emotional intelligence as an intervening variable. The focus of this research is to find out the most commonly adopted gender identity trends, and their impact on the relationship between leaders and subordinates. This research uses data collection method with questionnaire method for civil servants. The results showed that gender role identity: masculinity, directly affects leader-member exchange (LMX), and can affect indirectly with emotional intelligence as an intervening variable.